The main directions of migration and legal policy of the Republic of Kazakhstan in the context of the formation of migration law (Journal of actual problems of jurisprudence, 2019)
This article discusses the formation of the legal migration policy of the Republic of Kazakhstan. On thetheoretical and legal positions of the comparative analysis of the existing definitions of legal migrationpolicy, suggested author’s definition. It is proved that regular updating of the migration legislation meet therealities of the modern state-legal development of the Republic of Kazakhstan. It was determined that themain directions of migration and legal policy of the Republic of Kazakhstan are implemented in the followingareas: the formation of the population, repatriation, industrial-innovative development of Kazakhstan andthe regulation of internal migration flows.Keywords: migration, the formation of the population, repatriation, internal migrants, migration and legalpolicy, immigration legislation.